First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Evaluation of interannual variability of Arctic and Antarctic ozone loss since 1989 - Goutail, Florence; Pazmino, Andrea; Pommereau, Jean-Pierre; Lefèvre, Franck; Godin-Beekmann, Sophie; Hauchecorne, Alain; Lecouffe, Audrey; Clerbaux, Cathy; Boynard, Anne; Hadji-Lazaro, Juliette; Chipperfield, Martyn; Feng, Wuhu; et al. (2021)
Ozone depletion over Polar Regions is monitored each year by satellite and ground-based instruments. The first signs of healing of the ozone layer linked to the decrease of ozone destructive substances (ODSs) were observed in Antarctica using different metrics (ozone mean values, ozone mass deficit, area of the ozone hole) and simple or sophisticated models. Chemistry climate models predict that climate change will not affect expected ozone recovery over Antarctica but will accelerate recovery in the Arctic due to the possible enhancement of the Brewer Dobson circulation. However, ozone loss observations by SAOZ UV-Vis spectrometers do not show a clear sign of recovery in the latter region. In addition, a record of 38% ozone loss in 2010/2011 and 2019/2020 was estimated. In this study, the vortex-averaged ozone loss in the last three decades will be evaluated for both Polar Regions using the passive ozone tracer of two chemical transport models (REPROBUS and SLIMCAT CTMs) and total ozone observations from SAOZ and satellite observations (IASI/METOP and Multi-Sensor Reanalysis (MSR-2)). The tracer method allows us to determine the evolution of the daily rate of ozone destruction, and the amplitude of the cumulative loss at the end of the winter. The cumulative ozone destruction in the Artic varies between 0-10% in relatively warm winters with short vortex duration to up to 25-38% in colder winters with longer vortex persistence, while in Antarctica it is mostly stable, around 50%. Interannual variability of 10-days average rate will be analyzed and compared between both hemispheres as well as the timing to reach different thresholds of absolute ozone loss values. Finally, linear trend of ozone loss and temperature since 2000 will be estimated in both Polar Regions in order to evaluate possible ozone recovery.
Publication Title: EGU General Assembly 2021 Place: Online, Germany
Keywords: Antarktis; klimaendringer; miljøovervåking; ozonlaget; polarområdene

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Decolonising Antarctica - Mancilla, Alejandra (Philosophies of polar law, 2021)
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; polarområdene; rettsfilosofi

Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D; et al. (Environmental Modelling & Software, 2021)
Quantarctica (https://www.npolar.no/quantarctica) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40oS), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier.
Keywords: Antarktis; Sørishavet; geografi; kartografi; polarområdene

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Satellite and ground based estimates for ice surface velocities in the part of central Dronning Maud Land, East Antarctica: Implications for ice flux calculations - Thakur, Praveen K; Swain, Ashit K; Dhote, Pankaj R; Kumar, Pradeep; Kaushik, Suvrat; Gajbhiye, Deepak; Mahagaonkar, Anirudha; Sharma, Vishal; Dharwadkar, Amit; Aggarwal, S P; Beg, Javed; Chauhan, Prakash; et al. (Polar Science, 2021)
The ice sheet and glaciers of Antarctica and Greenland represent the largest sources of freshwater on planet Earth. The understanding and quantification of their dynamic properties such as albedo, precipitation, ice mass movement, and ice elevation changes are critical for the improved climate and mass balance models. The present study utilizes space-borne optical and synthetic aperture radar (SAR) imagery to measure the ice surface velocity at high spatial resolution for a part of the central Dronning Maud Land (cDML), East Antarctica. The datasets from Landsat-8 and Sentinel-1 SAR satellite are used for ice stream velocity estimation using feature-offset tracking and differential interferometric SAR (DInSAR) methods. The derived velocity products are validated with ground based stakes network at annual time scale. The fundamental ice flow laws are used to estimate the ice outflux or discharge for selected ice stream drainage basins of cDML at fluxgate locations. The ice stream basin has been delineated using combination of elevation, slope and continental scale velocity maps. The ice influx for study area is estimated using ECMWF fifth generation reanalysis (ERA5) and Regional Atmospheric Climate Model (RACMO) v2.3 model outputs. The estimated influx and outflux are in the ranges of 0.18–4.167 Gt/y and 0.201 to 1.278 Gt/y respectively, indicating net positive mass balance for the selected area.
Keywords: Dronning Maud Land; glasiologi; innlandsis; polarområdene